2019
DOI: 10.1002/alr.22452
|View full text |Cite
|
Sign up to set email alerts
|

Virtual coach: the next tool in functional endoscopic sinus surgery education

Abstract: BackgoundFunctional endoscopic sinus surgery (FESS) can be challenging as novices become accustomed to handling endoscopes and instruments while navigating complex sinonasal anatomy. Experts demonstrate fluid and efficient motions when addressing pathology. The training process from novice to expert relies on hands‐on experience in cadaveric laboratories and preceptorship models that require significant time and expense. This study aims to validate the use of a virtual coach to guide users step‐by‐step through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…The incidence of chronic sinusitis is relatively high. Thus, in the clinical treatment of this disease, nasal endoscopic surgery is often used as the local anatomical structure can be clearly observed, meanwhile, the diseased tissue can be understood and targeted in time to effectively restore the basic functions of the sinuses and nasal cavity [ 14 ]. Although nasal endoscopic surgery could effectively improve the therapeutic effect, it will inevitably increase the secretion of inflammatory mediators due to invasive operations.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of chronic sinusitis is relatively high. Thus, in the clinical treatment of this disease, nasal endoscopic surgery is often used as the local anatomical structure can be clearly observed, meanwhile, the diseased tissue can be understood and targeted in time to effectively restore the basic functions of the sinuses and nasal cavity [ 14 ]. Although nasal endoscopic surgery could effectively improve the therapeutic effect, it will inevitably increase the secretion of inflammatory mediators due to invasive operations.…”
Section: Discussionmentioning
confidence: 99%
“…real-time data to users has been reported. 15,16 A mixedreality surgical simulator that could mimic tissue reactions, such as oozing or bleeding, could yield promising results. Additionally, it is worth noting that in teaching-related studies, there is a concern that the results may always be positive because the trainees are taught for the exam.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unnecessary damage to tissue that was observed to be a common weakness among the residents also suggested that we should help them by improving the simulator in the future. A training tool based on virtual reality technology, which provides immediate haptic feedback and objective real‐time data to users has been reported 15,16 . A mixed‐reality surgical simulator that could mimic tissue reactions, such as oozing or bleeding, could yield promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the VR can be used in the surgical simulation, allowing modernization of training and its transition from the practice of simple exercises into a fully-immersive environment experience. In a recent study, the use of a virtual coach was tried guiding a group of surgeons using surgical videos, auditory, and visual cues ( 70 ). In AuR, the real-world environments are combined with computer-generated sounds, text, and graphics.…”
Section: Technological Innovationmentioning
confidence: 99%